Obtenção de carvão a partir de casca de soja e aplicação na adsorção de herbicidas - Franca, Roberta Sorhaia Samayara Sousa Rocha de (2019)
The soy husk is one of the most abundant waste in Brazil. The adsorption processes are among the alternatives for the use of this residue. Pesticides are not effectively removed by conventional water treatment, processes such as adsorption are efficient in removing this pollutant. The objective of the present work was to obtain charcoal from soybean hulls and to evaluate its efficiency in the adsorption of the herbicides Jaguar® and Trueno®. Initially, the photodegradation of herbicides in water was evaluated over 30 days and it was found that both herbicides did not degrade, Jaguar® increased 10% of the absorbance and the value of Trueno® remained at the end of 30 days. In the physical-chemical characterization of the vegetable biomass, the soybean hull had a zero load point of 8.0, and the lignin results were from 7.96 (35 mesh) to 10.1% (60 mesh) and the higher the lignin content in the biomass, the higher the charcoal yield. Then, the soybean husk was carbonized and herbicide adsorption tests were carried out and the results, compared with commercial activated carbon, showed equal efficiency. Afterwards, activation studies of the carbonized soybean house were made. Chemical activation was performed in contractions of 1, 2 and 3% in the particle sizes of 20 and 35 mesh. The activated charcoals were characterized in terms of methylene blue index, iodine number. Finally, studies on the adsorption of the herbicides Jaguar® and Trueno® were carried out with the activated carbons obtained, resulting in removal above 99,99% for all charcoals. The charcoal obtained from the soybean hull presented itself as a sustainable and low-cost alternative in the removal of herbicides and dyes, presenting results statistically equal to those of commercial coal.